Solar system : our place in space - Mosco, Rosemary (Science comics (First Second (Firm)), 2018)
Get up close and personal with Earth's nearest neighbors--Venus with its acid rainstorms, Saturn and its rings of ice, and the heart of it all, the Sun. Humans have always been fascinated by outer space and we're learning more about our solar system every day. Did you know that our Solar System was born from a cloud of cosmic dust? That Jupiter's red spot is really a raging storm? Join Sara, Jill, and their space-faring pets on a quest to learn more about the wonders of our Solar System--and beyond!--Adapted from page 4 of cover.